Bedside lamp timer / Syazwan Jasni and Norazman Saad - Jasni, Syazwan; Saad, Norazman (2003)
The course KEU 380 or Project 2 is one of the subjects that compulsory for student in their final year of Diploma in Electrical Engineering. The bedside lamp timer is the choice of our project for this course. The bedside lamp timer is types of a timer, which will cut the supply to the lamp that, connect to this circuit. The circuit of the timer is not as complicated as other circuit and it is easy to use. When this circuit connected to the lamp, it will automatically cut the supply to the lamp when certain button is pressed in 30 minutes. This project is useful when we want to go to bed at night and forgot to switch off the bedside lamp. In addition, this circuit can be use with old television set, radio and table fan. The commercial value of bedside lamp timer maybe good after making the project more space saving, low in cost and reliable.